Endocrine and Neuroendocrine Surgery - Howe, James R. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book brings together recognized experts in the field to describe their current techniques for the surgical treatment of diseased thyroid, parathyroid, and adrenal glands, as well as neuroendocrine tumors of small bowel, pancreas, liver, and skin. For each procedure, indications, operative steps, potential pitfalls and complications, and postoperative management are presented. The clear descriptions coupled with informative and beautiful illustrations will give the reader new perspectives and insights into the anatomy and conduct of these procedures. Endocrine surgery has been an area of special interest to surgeons for well over a century, while the increasing incidence of neuroendocrine tumors has more recently led to greater attention to these neoplasms. Significant advances have been made in a variety of areas, the most recent being the introduction of minimally invasive methods of removing diseased glands, and the improved understanding of the natural history of neuroendocrine tumors. .
Keywords: Medicine.; Endocrinology.; Oncology.; Minimally invasive surgery.; elektronické knihy; electronic books